If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8g + -4g + 10 = -10 + -10g Reorder the terms: 10 + -8g + -4g = -10 + -10g Combine like terms: -8g + -4g = -12g 10 + -12g = -10 + -10g Solving 10 + -12g = -10 + -10g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '10g' to each side of the equation. 10 + -12g + 10g = -10 + -10g + 10g Combine like terms: -12g + 10g = -2g 10 + -2g = -10 + -10g + 10g Combine like terms: -10g + 10g = 0 10 + -2g = -10 + 0 10 + -2g = -10 Add '-10' to each side of the equation. 10 + -10 + -2g = -10 + -10 Combine like terms: 10 + -10 = 0 0 + -2g = -10 + -10 -2g = -10 + -10 Combine like terms: -10 + -10 = -20 -2g = -20 Divide each side by '-2'. g = 10 Simplifying g = 10
| -1+2j=j-8 | | -6+2=y | | -9p-2=-7-6p-2p | | 2f+6=f | | 4(3y-4)-(2y+3)= | | 6-9y=33 | | 7-2v=-9v | | 5/8y=x | | x^2+12x+35=35 | | (-x^2-50x-625)/(-3x-75) | | 7-4y=15 | | bp=4a-ap | | -143=-1x | | 5/6d=11/18 | | 2(x+1)=46 | | 4(p+2)-2(1-p)-4=0 | | m^2+5m-126=0 | | 5=5(u+4)-8u | | -8=x+11over-2 | | log(2k-4)=1+logk | | 15n^3+16n^2-7n=0 | | 12x+5y=-105 | | 5z-(z-18)=6-(z+15) | | 2(2/.5l/l)=40 | | -12+6=-2(x+5) | | 2(2/.5l/l | | 2(5x+4)-6= | | (5-3i)+(-7-2i)=0 | | 18+4=723214 | | -6(2t+3)=-78 | | (b-6)(b-4)=0 | | 3r^2-12r-135=0 |